The functional role of the Carabelli trait in early and late hominins. Issue 145 (August 2020) - Fiorenza, Luca; Menter, Colin G.; Fung, Sarah; Lee, Jinyoung; Kaidonis, John; Moggi-Cecchi, Jacopo; Townsend, Grant; Kullmer, Ottmar
Abstract: The Carabelli trait is a dental feature that forms along the lingual margin of the protocone of deciduous and permanent maxillary molars. It is variably expressed, ranging from a small pit or furrow to a large cusp, and its development seems to be associated with crown size and molar cusp spatial configuration. The degree of expression of the Carabelli trait differs systematically between hominin taxa, and for this reason, it has been used extensively in the reconstruction of their phylogeny. However, the functional implications of having a large Carabelli trait remain unclear. In this study, we analyze the macrowear pattern of maxillary molars of early and late hominins using the occlusal fingerprint analysis method, an approach based on digital models of teeth that helps in reconstructing occlusal dynamics occurring during mastication. Tooth crowns with a small Carabelli cusp generally exhibit larger wear contact areas that extended cervically, while two additional new occlusal contact areas are common in teeth characterized by a large Carabelli cusp. These wear areas are created at the beginning of the chewing cycle, when occluding with the slopes of the lingual groove of the lower molars, between the metaconid and entoconid cusps. Advancing tooth wear leads to a slight enlargement of Carabelli occlusal contacts increasing their functional area. A steep inclination could be mechanically important in food reduction and in balancing the functional load distribution during mastication contacts. Steep wear areas are particularly developed in primates that process foods characterized by tough and fibrous textural properties. Future biomechanical and microwear texture analyses could provide additional information on the mechanical adaptation of this dental trait.